Architecture Design of the Cladding Part Modeling System - Yang Junru; Sun Hong; Zhang Lili; Zhang Daozhong; Zhang Yuekan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The cladding part is a new type of layered heterogeneous material part with three layers of the substrate, the interface and the clad. According to the part unique material composition and structural characteristic, based on the hierarchical modeling method, the software architecture design of the cladding part modeling system was researched. Using UML (Unified Modeling Language) and the software Rational Rose, the use cases, static logic, dynamic logic and physical deployment of the modeling system were described with the use case diagram, class diagrams, communication diagrams, components diagram and deployment diagram. The research results can guide the development process of the cladding part modeling system with high stability and reliability. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3274